Interdisciplinary Teaching Activities for High School Integrated to Vocational Education Promoting Reflections on Industry 4.0 Technologies and Their Implication in Society - Vieira, Mariana Calaon Criscolin; Gouveia, Riama Coelho; Dias, Andre Luis (Journal of Technical Education and Training, 2022)
The educational system in Brazil, especially the high school level, is characterized by a division, offering a general and humanist formation for the economic elite, and direct preparation for labor, for the working-class. Aiming to overcome this duality and contribute to the polytechnic formation of vocational education students, this paper presents and analyzes interdisciplinary teaching activities that discuss the relationships between Industry 4.0 technologies, production systems, and education.  The educational product, developed and applied based on the action research methodology, consisted of identifying the students' prior knowledge, three units of teaching activities, and a final evaluation questionnaire. According to the students' background and their suggestions, the content and didact methodology of each unit was selected, including the history of industrial revolutions, technologies arising from Industry 4.0 (internet of things, data mining, and cloud computing), the challenges of the fourth Industrial Revolution on the economy and labor. Didact methodologies include dialogic lecture based on slides, hands-on practical activity experimenting Industry 4.0 technologies through free online applications, and debate. Interdisciplinary activities were developed at the Federal Institute of Education, Science and Technology of São Paulo, involving students of the 4th year (last) of high school integrated into vocational education with a qualification in Industrial Automation. During the application it was observed that the use of educational product led to considerable levels of motivation and promoted reflections related to the impact of the industry 4,0 technologies in society and employment. Also, it has been verified that the didact sequence increases the student capacity to identify problems and propose possible solutions; understand labor different dimensions (technology, employment, politics, and economics); use strong argumentation based on reliable sources, proposing possible interventions. Thus, the interdisciplinary approach of technological development, considering not only the technical concepts but also the historical and sociological issues related to the application of technologies in the productive system, contributes to a critical teaching-learning process and the omni-lateral formation in vocational education.